Conductive material and method for manufacturing same
By using a copper or copper alloy base material, bottom layer, Cu-Sn alloy layer and matte Sn plating structure in the conductive material of the vehicle-mounted terminal, the problem of high contact resistance under low contact pressure is solved, and the low dynamic friction coefficient and high heat resistance of the conductive material are achieved.
Patent Information
- Application Number
- CN202380061023.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-25
- Filing Date
- 2023-07-14
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art is difficult to effectively reduce the contact resistance of vehicle-mounted terminals under low contact pressure (<2N), and the kinetic friction coefficient and heat resistance of the conductive material are insufficient.
A base material formed of copper or copper alloy is used to form a structure of a bottom layer composed of Ni, Co, and Fe, a Cu-Sn alloy layer and a Sn layer, in which a part of the Cu-Sn alloy layer is exposed from the Sn layer side surface, and a matte Sn plating layer with an area of more than 50 μm square on the Sn layer side surface is formed to improve the kinetic friction coefficient and heat resistance of the conductive material.
It achieves a significant reduction in contact resistance under low contact pressure (<2N), while having sufficient low dynamic friction coefficient and good heat resistance, enhancing the overall performance of the conductive material.
Smart Images

Figure CN119698499A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive material and a method for producing the same. Background Art
[0002] As electronic control in automobiles becomes more versatile and sophisticated, the number of poles in automotive terminals has increased, and the insertion force of the terminals has increased accordingly. Therefore, from the perspective of reducing the burden on operators in the automobile assembly process and preventing assembly errors, the conductive material used for the terminals needs to have a low dynamic friction coefficient. In addition, since automotive terminals may be used at high temperatures for a long time, the conductive material used for the terminals needs to have sufficient heat resistance.
[0003] Patent document 1 discloses a material as a conductive material with a low dynamic friction coefficient, for example, the arithmetic mean roughness of the material surface when the cutoff value is 0.8 mm is within a specified range, and the area ratio of the region where the Cu-Sn alloy layer is exposed to the region where the Cu-Sn alloy layer is not exposed is within a specified range. In addition, Patent document 1 also states that the material can suppress the increase in contact resistance after long-term use at high temperature.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-115210 Summary of the invention
[0007] Problems to be solved by the invention
[0008] With the autonomous driving and electrification of automobiles in recent years, the further miniaturization of vehicle-mounted terminals is being promoted. The miniaturization of the terminal leads to a smaller spring structure, so the contact pressure of the terminal is reduced. Therefore, there is a need for a conductive material that shows high conductivity (i.e., low contact resistance) even under low contact pressure. However, the prior art described in Patent Document 1 does not study the contact resistance under low contact pressure (<2N), which shows that there is room for further improvement.
[0009] The present invention has been proposed in view of the above circumstances, and one of its objects is to provide a conductive material and a method for manufacturing the same, which have a sufficiently low dynamic friction coefficient and sufficient heat resistance and can sufficiently reduce the contact resistance under a low contact pressure (<2N).
[0010] Means of solving the problem
[0011] A first aspect of the present invention is a conductive material comprising, in order: a base material formed of copper or a copper alloy; one or more base layers formed of any one or more selected from the group consisting of Ni, Co and Fe; a Cu-Sn alloy layer; and a Sn layer, wherein:
[0012] A portion of the Cu—Sn alloy layer is exposed on the Sn layer-side surface of the conductive material.
[0013] In a 250 μm square region containing 50% by area or more of the Sn layer on the Sn layer side surface of the conductive material, an arithmetic mean height evaluated with a cutoff value of 25 μm was 0.03 μm or more.
[0014] Aspect 2 of the present invention is the conductive material according to aspect 1, wherein the arithmetic mean height is 0.05 μm or more.
[0015] Aspect 3 of the present invention is a conductive material according to aspect 1 or 2, wherein the arithmetic mean roughness in at least one direction of the bottom layer side surface of the base material is 0.15 μm or more, and the arithmetic mean roughness in all directions is 3.0 μm or less.
[0016] A fourth aspect of the present invention is a method for producing a conductive material, comprising:
[0017] forming one or more base layers on a base material formed of copper or a copper alloy, wherein the base layer is composed of one or more selected from the group consisting of Ni, Co and Fe;
[0018] After forming a Cu layer and a Sn layer in sequence on the bottom layer, a reflow treatment is performed to obtain a Cu-Sn alloy layer;
[0019] After the reflow treatment, a matte Sn plating layer with a plating thickness of 0.025 to 0.25 μm is formed;
[0020] In the matte Sn plated layer surface, a portion of the Cu—Sn alloy layer is exposed.
[0021] A fifth aspect of the present invention is the production method according to the fourth aspect, wherein the matte Sn plating layer has a plating thickness of 0.05 to 0.20 μm.
[0022] Mode 6 of the present invention is a manufacturing method according to mode 4 or 5, wherein the formation of the base layer is carried out by forming the base layer on the surface of the roughened base material, and the roughening method is to make the arithmetic mean roughness in at least one direction greater than 0.15μm and the arithmetic mean roughness in all directions less than 3.0μm.
[0023] Effects of the Invention
[0024] According to the embodiments of the present invention, a conductive material and a method for manufacturing the same can be provided, which have a sufficiently low dynamic friction coefficient and sufficient heat resistance and can sufficiently reduce contact resistance under a low contact pressure (<2N). BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1A This is an optical microscope image of the Sn layer side surface of the conductive material of Test No. 1.
[0026] Figure 1B This is an optical microscope image of the Sn layer side surface of the conductive material of Test No. 2.
[0027] Figure 1C This is an optical microscope image of the Sn layer side surface of the conductive material of Test No. 3.
[0028] Figure 1D This is an optical microscope image of the Sn layer side surface of the conductive material of Test No. 4.
[0029] Figure 2A This is a secondary electron (SE) image of the Sn layer side surface of the conductive material of Test No. 1 obtained from SEM.
[0030] Figure 2B This is a backscattered electron (BSE) image of the Sn layer side surface of the conductive material of Test No. 1 obtained from a SEM.
[0031] Figure 3A This is a cross-sectional SEM image parallel to the stacking direction of each layer of the conductive material in Test No. 1.
[0032] Figure 3B This is a cross-sectional SEM image parallel to the stacking direction of each layer, including a portion where a portion of the Cu—Sn alloy layer is exposed from the Sn layer side surface, in the conductive material of Test No. 4.
[0033] Figure 3C This is a cross-sectional SEM image parallel to the stacking direction of each layer in the conductive material of Test No. 4, of a portion where the Cu—Sn alloy layer is not exposed from the Sn layer side surface.
[0034] Figure 4 is a schematic diagram of a device for evaluating the dynamic friction coefficient.
[0035] Figure 5 This is a schematic diagram of an apparatus for evaluating micro-sliding wear resistance. DETAILED DESCRIPTION
[0036] The present inventors have conducted studies from various perspectives in order to realize a conductive material having a sufficiently low dynamic friction coefficient and sufficient heat resistance and capable of sufficiently reducing the contact resistance under a low contact pressure (<2N).
[0037] It was discovered that by forming a structure having a base material, a base layer, a Cu-Sn alloy layer and a Sn layer in sequence, and by exposing a portion of the Cu-Sn alloy layer with higher hardness from the side surface of the Sn layer, the conductive material can be endowed with sufficient heat resistance and the dynamic friction coefficient of the conductive material can be sufficiently reduced.
[0038] In addition, it was found that in a 250μm square area containing 50% or more of the Sn layer on the side surface of the Sn layer, the arithmetic mean height (hereinafter also referred to as "Sa") evaluated by setting the cutoff value to a very narrow interval of 25μm (i.e., excluding the influence of the surface unevenness of the base material with a wide interval of unevenness greater than 25μm) is 0.03μm or more, and the contact resistance can be sufficiently reduced even at a low contact pressure (<2N). This is believed to be because the oxide formed on the surface of the Sn layer usually causes the contact resistance to increase, and at this time, the oxide is easily destroyed even at a low contact pressure by having the above-mentioned surface shape, so the contact resistance can be reduced even at a low contact pressure.
[0039] It was also found that, as a method for producing the conductive material, when forming the outermost Sn layer, unlike the conventional glossy Sn plating layer disclosed in Patent Document 1, a matte Sn plating layer is formed with a predetermined thickness, thereby obtaining a conductive material having the above-mentioned Sa.
[0040] Based on the above, a conductive material can be realized which has a sufficiently low dynamic friction coefficient and sufficient heat resistance and can sufficiently reduce the contact resistance under a low contact pressure (<2 N). The above mechanism does not limit the technical scope of the embodiments of the present invention.
[0041] The following describes in detail each requirement specified in the embodiment of the present invention.
[0042] The conductive material of an embodiment of the present invention comprises, in order: a base material formed of copper or a copper alloy; one or more base layers composed of any one or more selected from the group consisting of Ni, Co and Fe; a Cu-Sn alloy layer; and a Sn layer, wherein a portion of the Cu-Sn alloy layer is exposed on the Sn layer side surface of the conductive material, and a 250 μm square area containing more than 50 area % of the Sn layer on the Sn layer side surface of the conductive material has an arithmetic mean height of 0.03 μm or more evaluated with a cutoff value of 25 μm.
[0043] Based on the above, it is possible to have a sufficiently low dynamic friction coefficient and sufficient heat resistance, and to sufficiently reduce the contact resistance under a low contact pressure (<2 N). Each layer is described in detail below.
[0044] <Base material>
[0045] In the embodiment of the present invention, the base material is formed of copper or a copper alloy. As the material of the base material, for example, in addition to pure copper, various copper alloys such as Cu-Ni-Si, Cu-Ni-Sn-P, Cu-Fe-P, Cu-Zn, Cu-Cr-Ti-Si, and Cu-Mg can also be used.
[0046] The shape of the base material is not particularly limited, for example, it can be a plate, a strip, or processed into the shape of a terminal. The surface shape of the base material is also not particularly limited, and it can be flat or concave and convex. In the method for manufacturing a conductive material of an embodiment of the present invention described later, from the viewpoint of easily exposing a portion of the Cu-Sn alloy layer from the surface, it is preferred that the arithmetic mean roughness (hereinafter also referred to as "Ra") in at least one direction of the base side surface of the base material when the cutoff value is 0.8 μm is greater than 0.15 μm, and the Ra in all directions is less than 3.0 μm. The Ra of the base side surface of the base material can be measured, for example, using a surface roughness meter based on JIS B0601:2001. In addition, the Ra of the base side surface of the base material can also be obtained from a cross-sectional image parallel to the stacking direction of each layer of the conductive material.
[0047] When the base material is in a plate shape, the thickness is not particularly limited, and may be, for example, 0.05 mm or more and 2 mm or less.
[0048] <Ground Floor>
[0049] The bottom layer is one or more layers consisting of any one pure metal selected from the group consisting of Ni, Co and Fe or an alloy of two or more. The bottom layer is used to inhibit the diffusion of Cu and alloy elements in the base material to the material surface, and the increase in contact resistance can be suppressed even after long-term use at high temperatures. In addition, the diffusion of the bottom layer itself to the material surface can be suppressed by the Cu-Sn alloy layer described later. In addition, by forming the bottom layer, the corrosion resistance of the material to sulfur dioxide gas is improved.
[0050] In order to suppress the pit defects in the base layer and further exert the above-mentioned effect, the average thickness of the base layer (when the base layer is two layers, the average of the total thickness of the two layers) is preferably 0.1 μm or more. On the other hand, in order to reduce costs and ensure forming processability, the average thickness of the base layer is preferably 3.0 μm or less. In addition, the average thickness of the base layer can be measured, for example, using an X-ray fluorescence film thickness meter.
[0051] The surface shape of the base layer is not particularly limited, and may reflect, for example, the shape of the base layer side surface of the base material.
[0052] <Cu-Sn alloy layer>
[0053] The Cu-Sn alloy layer is formed of an alloy of Cu and Sn. The Cu-Sn alloy layer can be composed of only η phase (Cu6Sn5) or ε phase (Cu3Sn) and η phase, for example. When the Cu-Sn alloy layer is composed of ε phase and η phase, the ε phase can be formed between the bottom layer and the η phase and can be in contact with the bottom layer. Because the ε phase is harder than the η phase, if the ε phase exists, the Cu-Sn alloy layer becomes harder and the friction coefficient can be further reduced, so it is preferred. In addition, for example, if it is a Ni bottom layer, the (Cu, Ni) 6Sn5 alloy layer can be formed after reflow treatment.
[0054] The Cu-Sn alloy layer is partially exposed from the Sn layer side surface of the conductive material of the embodiment of the present invention, and the entire surface is not covered by the Sn layer. As a result, the dynamic friction coefficient of the conductive material can be sufficiently reduced. In addition, a portion of the Cu-Sn alloy layer is exposed from the Sn layer side surface of the conductive material, which can be confirmed by, for example, using a SEM (scanning electron microscope) to obtain a backscattered electron (BSE) image of the Sn layer side surface of the conductive material.
[0055] Figure 2B An example of a BSE image of a conductive material (Test No. 1) according to an embodiment of the present invention is shown in FIG. Figure 2B In the BSE image of the Sn layer side surface of the conductive material, a darker area caused by the Cu-Sn alloy layer 1 and a brighter area caused by the Sn layer (here, the matte plated layer 2b) can be observed. When a darker area caused by the Cu-Sn alloy layer 1 can be observed in the BSE image of the Sn layer side surface of the conductive material, it can be determined that a portion of the Cu-Sn alloy layer is exposed from the Sn layer side surface of the conductive material.
[0056] The area ratio of the exposed portion of the Cu-Sn alloy layer on the surface of the Sn layer side of the conductive material is preferably 10% or more. Thus, the dynamic friction coefficient of the conductive material can be further reduced. On the other hand, the area ratio of the exposed portion of the Cu-Sn alloy layer on the surface of the Sn layer side of the conductive material is preferably 50% or less, and more preferably 40% or less. Thus, the contact resistance of the conductive material can be further reduced. In addition, the area ratio of the exposed portion of the Cu-Sn alloy layer on the surface of the Sn layer side of the conductive material can be obtained by obtaining the above-mentioned BSE image, and using image analysis software (ImageJ 1.49 of free software) to binarize the obtained BSE image, and calculating the area ratio of the exposed portion of the Cu-Sn alloy layer by image analysis.
[0057] In order to reduce costs and ensure formability, the average thickness of the Cu-Sn alloy layer is preferably below 3.0 μm. On the other hand, based on the viewpoint of suppressing the diffusion of the underlying raw materials (Ni, Co and Fe) into the Sn layer, the average thickness of the Cu-Sn alloy layer is preferably above 0.2 μm. In addition, the average thickness of the Cu-Sn alloy layer can be measured, for example, using an X-ray fluorescence film thickness meter. Specifically, the value of the Sn component in the Cu-Sn alloy layer can be measured using X-ray fluorescence, and the average of the obtained Sn plating thickness can be used as the average thickness of the Cu-Sn alloy layer.
[0058] The Cu—Sn alloy layer may be continuous or discontinuous in a plane perpendicular to the stacking direction. When discontinuous, the Sn layer as the upper layer may be in direct contact with the lower layer (eg, base layer) in a portion of the region where the Cu—Sn alloy layer does not exist.
[0059] <Sn layer>
[0060] The Sn layer is disposed on the surface of the conductive material. The Cu—Sn alloy layer is partially exposed from the surface. That is, the Sn layer is discontinuous on the surface of the conductive material (in a plane perpendicular to the stacking direction).
[0061] In a 250 μm square area containing more than 50% of the Sn layer on the surface of the Sn layer side of the conductive material, the arithmetic mean height (Sa) evaluated with a cutoff value of 25 μm (i.e., excluding the influence of wide-spaced concavities and convexities higher than 25 μm such as the surface concavities and convexities of the base material) is 0.03 μm or more. As a result, the contact resistance of the conductive material can be sufficiently reduced due to the fact that the oxide film formed on the surface is easily destroyed. Sa is preferably greater than 0.05 μm, and more preferably greater than 0.07 μm. In addition, for example, when the cutoff value is higher than 25 μm for evaluation, the wide-spaced concavities and convexities that are not easily destroyed by the oxide film are also reflected in the arithmetic mean height. Therefore, when the cutoff value is higher than 25 μm for evaluation, even if the arithmetic mean height is greater than 0.03 μm, the contact resistance of the conductive material may not be sufficiently reduced.
[0062] The above-mentioned Sa can be obtained by measuring using a laser microscope in accordance with ISO 25178. In addition, whether or not a Sn layer of 50% by area or more is contained can be confirmed by a BSE image of the Sn layer side surface of the conductive material, in the same manner as the method for obtaining the area ratio of the exposed portion of the Cu-Sn alloy layer.
[0063] The Sn layer preferably has a convex portion with a height of H and a bottom width of W on the surface of at least one cross section parallel to the stacking direction, where H / W ≥ 0.15. Thus, the contact resistance of the conductive material can be further reduced. Here, the so-called bottom width W is the width in the direction along the surface of the Sn layer, and the height H is the height in the direction perpendicular to the surface. The average value of H is preferably greater than 0.1 μm. There is no particular limit on the upper limit of the average value of H, for example, it can be less than 1 μm. The average value of W is preferably less than 5 μm, more preferably less than 3 μm. There is no particular limit on the lower limit of the average value of W, for example, it can be greater than 0.1 μm. By satisfying these ranges, the contact resistance of the conductive material can be further reduced. For example, in the surface image of the Sn layer side of the conductive material, when the convex portion of the Sn layer is formed in a linear shape, a cross-sectional sample is made in the vertical direction relative to the linear convex portion, and the center of the linear convex portion is observed in the horizontal direction, thereby confirming whether the convex portion is the above-mentioned shape.
[0064] The conductive material according to the embodiment of the present invention may include a base material, a base layer, a Cu—Sn alloy layer, and a layer other than the Sn layer, within a range that can achieve the purpose.
[0065] The conductive material of the embodiment of the present invention can have a sufficiently low dynamic friction coefficient and sufficient heat resistance through the above structure, and can also sufficiently reduce the contact resistance under low contact pressure (<2N). In addition, in recent years, due to the vibration of the automobile engine and / or the vibration caused by the driving of the automobile, micro-slipping occurs between the contact points, the contact points are worn, and the phenomenon of increased contact resistance (micro-slip wear) has become a problem. The conductive material of the embodiment of the present invention also has sufficient resistance to micro-slip wear by utilizing the above structure. That is, the oxide on the surface of the Sn layer is destroyed and peeled off due to micro-slipping, and the accumulation of the peeled material promotes wear. In the embodiment of the present invention, because a part of the Cu-Sn alloy layer is exposed from the surface, the wear of the Sn layer and (the accumulation of oxides peeled off due to wear) are intermittent. Therefore, the conductive material of the embodiment of the present invention can reduce the wear associated with micro-slipping.
[0066] The manufacturing method of the conductive material of the embodiment of the present invention comprises the following steps: forming the base layer on the base material; after sequentially forming the Cu layer and the Sn layer on the base layer, performing a reflow treatment to obtain the Cu-Sn alloy layer; after the reflow treatment, forming a matte Sn plating layer with a plating thickness of 0.025 to 0.25 μm; and exposing a portion of the Cu-Sn alloy layer on the Sn layer side surface of the conductive material.
[0067] Hereinafter, each step will be described in detail.
[0068] <Forming a base layer on the base material>
[0069] Prepare the above-mentioned base material formed of copper or copper alloy, and form thereon a base layer consisting of one or more layers selected from the group consisting of Ni, Co and Fe. From the viewpoint of easy manufacturing, the base layer is preferably one or two layers selected from the group consisting of Ni layer, Co layer and Fe layer. The method for forming the base layer is not particularly limited, and it can be formed by a known method such as plating. At this time, it is preferred to form the base layer on the roughened base material surface so that the arithmetic mean roughness in at least one direction of the base material surface is 0.15μm or more, and the arithmetic mean roughness in all directions is 3.0μm or less. Thus, the Cu-Sn alloy layer can be exposed from the Sn layer side surface of the conductive material as described later. The roughening of the base material can be carried out, for example, by rolling (using a work roll roughened by grinding or shot peening), or by mechanical methods such as grinding or shot peening. In addition, physical methods such as ion etching, or chemical methods such as etching or electrolytic grinding can also be used.
[0070] <After forming the Cu layer and Sn layer in sequence on the base layer, a reflow treatment is performed to obtain a Cu-Sn alloy layer>
[0071] The Cu layer and the Sn layer can be formed by known methods such as plating. After the Cu layer and the Sn layer are formed in sequence, the Cu in the Cu layer and the Sn in the Sn layer diffuse into each other by reflow treatment to form a Cu-Sn alloy layer. At this time, the Cu layer may disappear completely, or a part of it may remain between the Cu-Sn alloy layer and the bottom layer. Similarly, the Sn layer may disappear completely or partially remain. In addition, assuming that the thickness of the Sn plating layer before the reflow treatment is (ts) and the thickness of the Cu plating layer is (tc), when ts / tc=2, both the Cu layer and the Sn layer are likely to disappear completely. In addition, when ts / tc<2, the Cu layer is likely to remain, and when ts / tc>2, the Sn layer is likely to remain (here, the remaining Sn layer is referred to as the "residual Sn layer"). In addition, when ts / tc>2, only the η phase will be formed in the equilibrium state, but through the reflow treatment conditions, the ε phase as a non-equilibrium phase can also be formed.
[0072] ts and tc are preferably ts / tc>2, tc is 0.1-1.5 μm, and ts is 0.35-3.15 μm. In this way, the ε phase can be formed and the Cu-Sn alloy layer can be adjusted to a preferred average thickness (0.2-3.0 μm). The reflow treatment conditions are preferably at the melting point of the Sn plating layer to 600°C for 3-30 seconds.
[0073] Here, when a base layer is formed on the roughened base material, the base layer and the Cu-Sn alloy layer may also have projections and depressions reflecting their shapes. In addition, when a portion of the Sn layer remains after the reflow treatment, the residual Sn layer may cause unevenness at the position corresponding to the concave portion of the roughened base material due to the flow of molten Sn into the concave portion during reflow. In other words, the layer composition at the position corresponding to the convex portion of the roughened base material may be base material / base layer / Cu-Sn alloy layer, while the layer composition at the position corresponding to the concave portion of the roughened base material may be base material / base layer / Cu-Sn alloy layer / residual Sn layer.
[0074] <After reflow treatment, a matte Sn plating layer with a plating thickness of 0.025 to 0.25 μm is formed>
[0075] By forming a matte Sn plating layer with a plating thickness of 0.025 to 0.25 μm, a Sn layer with fine convex portions can be obtained, and in a 250 μm square area containing 50% or more of the Sn layer, the arithmetic mean height evaluated with a cutoff value of 25 μm can be made to be above 0.03 μm. Here, the so-called matte Sn plating layer is a Sn plating layer formed using a plating bath that does not contain additives such as a brightener that refines the grains, and the plating bath contains, for example, SnSO4 and H2SO4. It is preferred to form a matte Sn plating layer with a plating thickness of 0.05 to 0.20 μm. As a result, in a 250 μm square area containing 50% or more of the Sn layer, the arithmetic mean height evaluated with a cutoff value of 25 μm can be made to be above 0.05 μm. It is more preferred to form a matte Sn plating layer with a plating thickness of 0.07 to 0.15 μm. As a result, in a 250 μm square region containing 50% by area or more of the Sn layer, the arithmetic mean height evaluated with a cutoff value of 25 μm can be set to 0.07 μm or more.
[0076] Here, when a base layer is formed on the roughened base material, the matte Sn plating layer can grow on the residual Sn layer existing at the position corresponding to the concave portion of the roughened base material. In other words, the layer composition at the position corresponding to the convex portion of the roughened base material can be base material / base layer / Cu-Sn alloy layer, and the layer composition at the position corresponding to the concave portion of the roughened base material can be base material / base layer / Cu-Sn alloy layer / Sn layer (i.e., residual Sn layer + matte Sn plating layer).
[0077] <Exposing a portion of the Cu-Sn alloy layer on the Sn layer side surface of the conductive material>
[0078] As a method for exposing a portion of the Cu-Sn alloy layer from the side surface of the Sn layer of the conductive material, various methods can be used. For example, by forming a base layer on the roughened base material mentioned above, a portion of the Cu-Sn alloy layer can be exposed from the side surface of the Sn layer of the conductive material at a position corresponding to the convex portion of the roughened base material. Even when the base layer is formed on a flat base material, a portion of the Cu-Sn alloy layer can be exposed by roughening the base layer in the same manner as the base material. In addition, for example, as in Japanese Patent Application Laid-Open No. 2013-174006, a Cu-Sn alloy layer with a dramatically undulating shape can be provided by adjusting the elements of the base layer and reflow treatment. In addition, after forming the base material / base layer / Cu-Sn alloy layer / Sn layer, a portion of the Cu-Sn alloy layer can be exposed by mechanically removing a portion of the Sn layer.
[0079] The method for producing a conductive material according to the embodiment of the present invention may include other steps within the scope of achieving the purpose.
[0080] Example
[0081] The following examples are given to more specifically illustrate the embodiments of the present invention. The embodiments of the present invention are not limited to the following examples, and can be appropriately modified within the scope of the above and the following purposes, and these are all included in the technical scope of the embodiments of the present invention.
[0082] Example 1
[0083] As the base material, a copper alloy plate (Cu-Ni-Sn-P system) with a thickness of 0.25 mm and rolled by rough rollers was used. The average arithmetic roughness Ra of the base material rolled by rough rollers was 0.48 μm in one direction and 0.49 μm in all directions. In addition, the surface roughness (arithmetic average roughness Ra) of the base material was measured using a contact surface roughness meter (Tokyo Seimitsu Co., Ltd.; SURFCOM 1400) based on JIS B0601:2001. The surface roughness measurement conditions were a cutoff value of 0.8 mm, a reference length of 0.8 mm, an evaluation length of 4.0 mm, a measurement speed of 0.3 mm / s, and a stylus tip radius of 5 μmR. The surface roughness was measured in a direction perpendicular to the rolling direction (the direction in which the maximum surface roughness can be calculated).
[0084] Next, a Ni plating layer was formed as a base layer on the roughened surface of the base material by a known method, with an average thickness of 0.3 μm. Specifically, the Ni plating solution before reflow treatment was the one described in Japanese Patent Publication No. 2004-68026, and the plating conditions were a current density of 5 A / dm 2 , bath temperature 60℃.
[0085] Then, a Cu plating layer and a Sn plating layer are formed on the base layer in sequence by a known method. Here, the thickness of the Cu plating layer (tc) and the thickness of the Sn plating layer (ts) before the reflow treatment are tc: 0.15μm and ts: 0.9μm, so that the Cu-Sn alloy layer can reach a preferred average thickness (0.2 to 3.0μm) while forming the ε phase. Specifically, the Cu plating solution and the Sn plating solution used are those described in Japanese Patent Publication No. 2004-68026, and the plating conditions are that when plating Cu, the current density is 3.5A / dm 2 , the bath temperature is 35℃, the current density is 3.0A / dm when Sn is plated 2 , bath temperature is 35°C.
[0086] Thereafter, a reflow treatment is performed under the condition of 232° C. or higher (substantial temperature) at which Sn melts.
[0087] After the reflow treatment, a matte Sn plating layer was formed to obtain the conductive material of Test No. 1. Specifically, the matte Sn plating layer was formed by plating a bath containing SnSO4 (80 g / L) and H2SO4 (80 g / L) at 3 A / dm 2 Here, the average Sn layer thickness before and after matte Sn plating was measured for the conductive material of Test No. 1 using an X-ray fluorescence film thickness meter, and the increase was taken as the average thickness of the matte Sn plating layer, which was 0.10 μm.
[0088] The thickness of the matte Sn plating layer was changed from the conductive material of Test No. 1 to produce Test No. 2 (matte Sn plating 0.05μm), Test No. 3 (matte Sn plating 0.025μm), and Test No. 4 (no matte Sn plating). In addition, from Test No. 1, the base material was changed to a 0.20mmt copper alloy plate (Cu-Ni-Sn system) rolled by a flat roller, and no base layer was formed, thereby producing the conductive material of Test No. 5. Furthermore, from Test No. 1, the matte Sn plating layer was changed to a glossy Sn plating layer, and the conductive material of Test No. 6 was produced. In addition, in the formation of the glossy Sn plating, the bath contained a plating solution containing a brightener (35g / L) in addition to SnSO4 (80g / L) and H2SO4 (80g / L), and the plating was carried out at 3A / dm 2 The current density is 2 to 8 seconds and the electricity is turned on.
[0089] The Sn layer side surface of the conductive material of Test No. 1 to 6 was observed using an optical microscope. As an example, Figure 1A to Figure 1C The optical microscope images of the conductive materials of Test Nos. 1 to 3 on which the matte Sn plating layer was formed are shown respectively. Figure 1DAn optical microscope image of the conductive material of Test No. 4 without the matte Sn plating is shown. Figure 1D As shown in the figure, the conductive material of test No. 4 has a flat surface because it does not have a matte Sn plating layer. Figure 1D In the figure, the darker area is the Cu-Sn alloy layer 1, and the brighter area is the residual Sn layer 2a. Figure 1D Conductive material of Test No.4, Figure 1A to Figure 1C The conductive materials of Test Nos. 1 to 3 have a matte Sn plating layer 2b shown by a darker area and have a greater surface roughness.
[0090] The Sn layer side surface of the conductive material of Test No. 1 to 6 was observed by SEM. As an example, Figure 2A The secondary electron (SE) image of the Sn layer side surface of the conductive material of Test No. 1 is shown in FIG. Figure 2B The backscattered electron (BSE) image is shown in Figure 2. Figure 2A From the SE image, it can be seen that the surface of the Sn layer side of the conductive material has at least a matte Sn plating layer 2b with fine protrusions and a flat Cu-Sn alloy layer 1. Figure 2B The BSE image of the conductive material shows more clearly that a portion of the Cu-Sn alloy layer 1 (relatively dark area) is exposed on the Sn layer side surface of the conductive material. In addition, in Tests No. 2 to 4 and 6, a portion of the Cu-Sn alloy layer 1 is also exposed on the Sn layer side surface of the conductive material, but in Test No. 5, no exposure of the Cu-Sn alloy layer 1 is confirmed. This is believed to be because the manufacturing method of the conductive material in Test No. 5 is different from that in Tests No. 1 to 4 and 6, and does not include a means of exposing a portion of the Cu-Sn alloy layer 1 such as roughening the base material.
[0091] Furthermore, the Sn layer side surfaces of the conductive materials of Test Nos. 1 to 6 were fully observed by SEM, and it was confirmed that the area ratio of the Sn layer was 50 area % or more in the entirety (ie, all 250 μm square regions).
[0092] Using SEM, a cross section parallel to the stacking direction of each layer of the conductive material of Test Nos. 1 to 6 was observed. As an example, Figure 3A The cross-sectional SEM image of the conductive material of Test No. 1 is shown in FIG. Figure 3B The cross-sectional SEM image of the portion where a portion of the Cu—Sn alloy layer 1 of the conductive material of Test No. 4 is exposed from the surface is shown. Figure 3C FIG. 4 shows a cross-sectional SEM image of a portion of the Cu-Sn alloy layer 1 of the conductive material of Test No. 4 that is not exposed from the surface. Figure 3B and Figure 3CAs shown, it can be seen that the conductive material of Test No. 4 is composed of the Cu-Sn alloy layer 1 and the residual Sn layer 2a, or the Sn layer side surface is composed of the residual Sn layer 2a, and the surface is flat. Figure 3A As shown, it can be seen that the conductive material of Test No. 1 has a matte Sn plating layer 2b on the surface. If the height is H and the width of the bottom is W, a convex portion with H / W ≥ 0.15 is formed (as an example, Figure 3A In the example, H (≒0.53) and W (≒1.33) of a convex part are described, and it can be seen that H / W of the convex part ≒0.40). In addition, Figure 3A It can be seen that the convex portion caused by the matte Sn plating layer 2b grows on the residual Sn layer 2a, not on the Cu-Sn alloy layer 1. Figure 3A to Figure 3C In the embodiment, the base layer 3 was confirmed under the Cu—Sn alloy layer 1. In addition, at least in the conductive material of Test No. 1, the average value of H was in the range of 0.1 to 1 μm, and the average value of W was in the range of 0.1 to 3 μm.
[0093] The following evaluations were further performed on the conductive materials of Test Nos. 1 to 6.
[0094] <Arithmetic surface height (Sa) evaluation>
[0095] Using a laser microscope (Olympus Corporation; OLS-4100), the Sa of the Sn layer side surface of the conductive materials of Test Nos. 1 to 6 was measured in accordance with ISO 25178. The surface roughness measurement conditions were a cutoff value of 25 μm and a 250 μm square as an evaluation area.
[0096] <Contact resistance evaluation>
[0097] The contact resistance of the conductive materials of Test No. 1 to 6 was evaluated using an electric contact simulator (manufactured by Yamazaki Seiki Laboratory). In this device, the contact resistance measurement probe is a gold wire, but in this test, a probe material (Cu-Ni base material (0.2mm) / Cu-Sn alloy layer (0.3μm) / Sn layer (0.7μm)) was prepared separately, and a fixture for mounting a female test piece as its hemispherical processing material (outer diameter: 0.55mm) was made. The female test piece was used as a contact resistance measurement probe so that it could contact the Sn layer side surface of the male test piece, which was a plate cut from each conductive material. Then, three measurements were performed using the four-terminal method under the conditions of an open circuit voltage of 20mV, a current of 10mA, and a load of 1N, and the average value was taken as the contact resistance value. In addition, the male side test piece was heated at 160℃×120h in the atmosphere, and the contact resistance before and after heating was measured.
[0098] As the evaluation criteria, regarding the initial contact resistance, ◎ (very excellent): less than 2.3 mΩ, ○ (excellent): 2.4 to 6.3 mΩ, △ (sufficient): 6.4 to 6.8 mΩ, × (insufficient): 6.9 mΩ or more, regarding the contact resistance after heating, ◎ (very excellent): less than 2.9 mΩ, ○ (excellent): 3.0 to 6.9 mΩ, △ (sufficient): 7.0 to 9.9 mΩ, × (insufficient): more than 10.0 mΩ.
[0099] <Evaluation of dynamic friction coefficient>
[0100] The shape of the recessed portion of the electrical contact of the mating type connection component is simulated using Figure 4 The dynamic friction coefficient of the conductive materials of Test No. 1 to 6 was evaluated using the device shown. Figure 4 As shown, the male test piece 10 of the plate cut from each conductive material is fixed on the horizontal platform 11, and the female test piece 12 of the hemispherical processed material (outer diameter: 0.55mm) of the above-mentioned probe material is placed thereon so that the Sn layer sides of each test piece are in contact with each other. Next, a load of 1.0N (weight 13) is applied to the female test piece 12 to press the male test piece 10, and a horizontal load measuring instrument (Aikoh Engineering Co., Ltd.; Model-2152) is used to measure the maximum friction force (unit: N) when the male test piece 10 is slid once in the horizontal direction. The sliding distance is 5mm and the sliding speed is 80mm / min. Figure 4 In the figure, 14 is a force sensor, the arrow is the sliding direction, and the male test piece 10 and the female test piece 12 both take the rolling vertical direction as the direction parallel to the sliding direction. Assuming the vertical resistance (load) is P (=1.0N), when the maximum friction force is F, the dynamic friction coefficient μ' is expressed as μ'=F / P. Four measurement tests are carried out for each conductive material, and the average value of the dynamic friction coefficient is obtained as the dynamic friction coefficient of the conductive material. The evaluation criteria for the dynamic friction coefficient are, ◎ (very excellent): less than 0.19, 0 (excellent): 0.20~0.44, △ (sufficient): 0.45~0.59, × (insufficient): more than 0.60.
[0101] <Evaluation of micro-sliding wear resistance>
[0102] Micro-sliding wear resistance is achieved by simulating the shape of the groove of the electrical contact of the mating type connection component. Figure 5Evaluation is performed using a sliding tester such as the one shown. First, the male test piece 5 of the plate cut from each conductive material is fixed on a horizontal platform 6, and the female test piece 7 of the hemispherical processed material (outer diameter: 0.55 mm) of the above-mentioned probe material is placed thereon so that the Sn layer sides of each test piece are in contact with each other. A load of 1.0 N (weight 8) is applied to the female test piece 7 to press the male test piece 5, and a constant current of 10 mA is applied between the male test piece 5 and the female test piece 8. The male test piece 5 is slid in the horizontal direction using a stepping motor 9, and the initial peak value of the contact resistance is measured. Three measurement tests are performed on each conductive material to obtain an average value, which is used as the contact resistance of each conductive material. The sliding distance is 50 μm, and the sliding frequency is 1 Hz. The arrow in the figure indicates the sliding direction. The evaluation criteria for micro-sliding wear resistance (initial peak value of contact resistance) are, (Very excellent): 2.3 mΩ or less, ○ (Excellent): 2.4 to 6.3 mΩ, △ (Sufficient): 6.4 to 6.8 mΩ, × (Insufficient): 6.9 mΩ or more.
[0103] The above results are summarized in Table 1.
[0104]
Table 1
[0105]
[0106] According to the results of Table 1, the following investigation can be conducted. The conductive materials of Test No. 1 to 3 all meet the requirements specified in the embodiments of the present invention, have a sufficiently low dynamic friction coefficient (less than 0.59), and have sufficient heat resistance (contact resistance after heating is less than 9.9 mΩ), and can make the contact resistance under low contact pressure (<2N) sufficiently low (initial contact resistance is less than 6.8 mΩ), and also have sufficient resistance to micro-sliding wear (initial peak of contact resistance is less than 6.8 mΩ). In addition, Test No. 1 and 2 can further reduce the contact resistance because they meet the preferred requirement of Sa ≥ 0.05. Specifically, both the initial contact resistance and the contact resistance after heating are excellent. Test No. 1 can further reduce the contact resistance because it meets the more preferred requirement of Sa ≥ 0.07. Specifically, both the initial contact resistance and the contact resistance after heating are very excellent.
[0107] On the other hand, the conductive materials of Test Nos. 4 to 6 did not satisfy the requirements specified in the embodiment of the present invention, and the initial contact resistance, the contact resistance after heating, or the dynamic friction coefficient were insufficient.
[0108] The conductive material of Test No. 4 did not form a matte Sn plating layer, Sa was less than 0.03 μm, and the initial contact resistance was insufficient.
[0109] The conductive material of Test No. 5 did not form a base layer, and the contact resistance after heating was insufficient. In addition, the Cu-Sn alloy layer was not exposed from the Sn layer side surface, and the dynamic friction coefficient was also insufficient.
[0110] The conductive material of Test No. 6 formed a glossy Sn plating layer instead of a matte Sn plating layer, and Sa was less than 0.03 μm. The initial contact resistance was insufficient, and perhaps due to this, the contact resistance after heating was also insufficient.
[0111] The present application claims priority based on Japanese Patent Application No. 2022-134358 filed on August 25, 2022. The entire disclosure of Japanese Patent Application No. 2022-134358 is incorporated herein by reference.
[0112] Description of Reference Numerals
[0113] 1Cu-Sn alloy layer
[0114] 2Sn layer
[0115] 2a Residual Sn layer
[0116] 2b Matt Sn coating
[0117] 3 Bottom layer
[0118] 5, 10 male test pieces
[0119] 6.11 Horizontal Platform
[0120] 7, 12 female test piece
[0121] 8.13 Weights
[0122] 9 Stepper Motor
[0123] 14 Force sensor
Claims
1. A conductive material comprising, in order: a base material formed of copper or a copper alloy; one or more base layers formed of any one or more selected from the group consisting of Ni, Co and Fe; a Cu-Sn alloy layer; and a Sn layer, wherein: A portion of the Cu—Sn alloy layer is exposed on the Sn layer-side surface of the conductive material. In a 250 μm square region containing 50 area % or more of the Sn layer on the Sn layer side surface of the conductive material, an arithmetic mean height evaluated with a cutoff value of 25 μm was 0.03 μm or more.
2. The conductive material according to claim 1, wherein The arithmetic mean height is greater than or equal to 0.05 μm.
3. The conductive material according to claim 1 or 2, wherein: In the bottom layer side surface of the base material, the arithmetic mean roughness in at least one direction is 0.15 μm or more, and the arithmetic mean roughness in all directions is 3.0 μm or less.
4. A method for manufacturing a conductive material, wherein: include: Forming one or more base layers composed of any one or more selected from the group consisting of Ni, Co and Fe on a base material composed of copper or a copper alloy; On the bottom layer, a Cu layer and a Sn layer are sequentially formed, and then a reflow treatment is performed to obtain a Cu-Sn alloy layer; After the reflow treatment, a matte Sn coating with a coating thickness of 0.025 to 0.25 μm is formed; In the matte Sn plated layer surface, a portion of the Cu—Sn alloy layer is exposed.
5. The manufacturing method according to claim 4, wherein: The matte Sn plating layer has a plating thickness of 0.05 to 0.20 μm.
6. The manufacturing method according to claim 4 or 5, wherein: The primer layer is formed by forming the primer layer on the surface of the base material that has been roughened so that the arithmetic mean roughness in at least one direction is 0.15 μm or more and the arithmetic mean roughness in all directions is 3.0 μm or less.
Citation Information
Patent Citations
Conducting material for connecting parts and manufacturing method therefor
JP2004068026A
Tin-plated copper alloy terminal material excellent in insertion-extraction property
JP2013174006A
Conductive material for connection part
JP2017115210A
Foreign object detection device and foreign object detection method
JP2022134358A